SARS-CoV-2 surveillance in captive animals at the belo horizonte zoo, Minas Gerais, Brazil - Anisleidy Pérez Castillo; João Victor Oliveira Miranda; Paula Luize Camargos Fonseca; Rennan Garcias Moreira; Luiza Campos Guerra de Araújo e Santos; Daniel Costa Queiroz; Diego Menezes Bonfim; Carlyle Mendes Coelho; Paula Cristina Senra Lima; Rafael Otávio Cançado Motta; Herlandes Penha Tinoco; Júlia Angélica Gonçalves da Silveira; et al. (Virology Journal)
Abstract Background The pandemic caused by SARS-CoV-2 has not only affected humans but also raised concerns about its transmission to wild animals, potentially creating natural reservoirs. Understanding these dynamics is critical for preventing future pandemics and developing control strategies. This study aims to investigate the presence of SARS-CoV-2 in wild mammals at the Belo Horizonte Zoo in Brazil, analyzing the virus's evolution and zoonotic potential. Methods The study was conducted at the Belo Horizonte Zoo, Minas Gerais, Brazil, covering a diverse population of mammals. Oropharyngeal, rectal, and nasal swabs were collected from 47 captive animals between November 2021 and March 2023. SARS-CoV-2 presence was determined using RT-PCR, and positive samples were sequenced for phylogenetic analysis. Consensus genomes were classified using Pangolin and NextClade tools, and a maximum likelihood phylogeny was inferred using IQ-Tree. Results Of the 47 animals tested, nine (19.1%) were positive for SARS-CoV-2. Positive samples included rectal, oropharyngeal, and nasal swabs, with the highest positivity in rectal samples. Three genomes were successfully sequenced, revealing two variants: VOC Alpha in a maned wolf (Chrysocyon brachyurus) and a fallow deer (Dama dama), and VOC Omicron in a western lowland gorilla (Gorilla gorilla gorilla). Phylogenetic analysis indicated potential human-to-animal transmission, with animal genomes clustering close to human samples from the same region. Conclusions This study highlights the presence of SARS-CoV-2 in various wild mammal species at the Belo Horizonte Zoo, emphasizing the virus's zoonotic potential and the complexity of interspecies transmission. The detection of different variants suggests ongoing viral evolution and adaptation in new hosts. Continuous monitoring and genomic surveillance of SARS-CoV-2 in wildlife are essential for understanding its transmission dynamics and preventing future zoonotic outbreaks. These findings underscore the need for integrated public health strategies that include wildlife monitoring to mitigate the risks posed by emerging infectious diseases.